Pollution characteristics, source apportionment and health risks assessment of fine particulate matter during a typical winter and summer time period in urban Taiyuan, China. Issue 10 (25th November 2020) - Zhang, Mei; Li, Zhiping; Xu, Min; Yue, Jianwei; Cai, Zongwei; Yung, Ken Kin Lam; Li, Ruijin
Abstract: The concentrations of ambient fine particulate matter (PM2.5 ) and its compositions in urban Taiyuan, China during a typical winter and summer time period in 2017 were measured to investigate the pollution characteristics, source apportionment and health risks assessment of PM2.5 pollution. The results demonstrated that the mean daily mass concentration of PM2.5 in winter (102.6 ± 6.2 μg/m 3 ) was higher than that in summer (65.0 ± 17.2 μg/m 3 ) during sampling. The relatively high concentrations of heavy metals (Zn, Pb, Cu, As, Ni, Cr and Cd), anion (SO4 2−, NO3 −, Cl − and F − ) and high-molecular-weight PAHs in PM2.5 were observed. The enrichment factors (EFs) values, special diagnostic ratios like ratios of NO3 − /SO4 2− and individual PAHs concentration ratio showed that coal combustion and vehicle emissions were the major sources of PM2.5 pollution. Health risk assessment illustrated that mean hazard indices for non-cancer and cancer risk of all analyzed metals were within the safe range. However, inhalation exposure to PM2.5 -bound PAHs had carcinogenic risk, while not indicating non-carcinogenic risk. Taken together, although PM2.5 pollution was alleviated to some extent, PM2.5 pollution in 2017 was still serious and PM2.5 was mainly originated from coal burning, especially, in which PM2.5 -bound PAHs in Taiyuan may pose a potential health risk.